Changes in the Ownership Structure of Polish Firms Changing the Stock Market - Wawryszuk-Misztal, Anna (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
The aim of this paper is to examine the changes of ownership structure of a sample of 28 firms that moved from alternative stock market (NewConnect) to the main stock market (Warsaw Stock Exchange). The research hypothesis states that changing the market results in an increase the ownership of financial institutions. A chosen variables depicting ownership structure were calculated before and after moving from one market to another. The results of nonparametric Wilcoxon test do not confirm the hypothesis, i.e. one cannot state that the ownership of financial institution increases. While it is possible to state that the free float increases and the ownership concentration decreases.